Connectionist models of neurocognition and emergent behavior : from theory to applications : proceedings of the 12th Neural Computation and Psychology Workshop - Davelaar, Eddy J. (Progress in neural processing, 2012)
This volume collects together most of the papers presented at the Twelfth Neural Computation and Psychology Workshop (NCPW12) held in 2010 at Birkbeck College (England). The conference invited submissions on neurocomputational models of all cognitive and psychological processes. The special theme of this conference was "From Theory to Applications", which allowed submissions of pure theoretical work and of pure applied work. This topic extended the boundaries of the conference and highlighted the extent to which computational models of cognition and models in general are integrated in the cogn.